Framework para gamificação de ambiente virtual de aprendizagem corporativo utilizando técnicas de minimização do gaming the system - Oliveira, Paulo Henrique de Souza (2023)
Gamification is gradually consolidating itself as an engagement tool in academia, however, the corporate environment has been realizing the potential of this approach for a long time, even without attributing the nomenclature directly associated with games. About virtual environments for the training and qualification of human resources, there is a lot of difficulty in defining gamification requirements capable of motivating this public and, in addition, predicting and treating unwanted behaviors, known as “gaming the system”, frequent in this sector. type of training. In this context, this work presents a framework on gamification of virtual learning environments in corporate education, considering user behavior, with teto definefic framework, adapting the 7 dimensions of the W2H in order to guide gamification in these environments, aiming to guarantee user satisfaction and success in a modular and adaptive way to different contexts. At the end, a case study is presented where the framework is applied in a real context. Finally, a case study is presented, where the framework is used in a real context. It details the steps of the process with a focus on implementation, where the tools used and the by-products obtained from the application are acquired. It was possible to perceive the benefits of using standardized development techniques to carry out a project, both in the result obtained and in the documents generated, which provide ease of reproduction and maintenance of the final product.